Negative electrode material, preparation method thereof and battery

By using a composite material composed of porous organic frame material and metal sulfide quantum dots to form an S-shaped heterojunction structure, the problems of lower specific capacity and growth of lithium dendrites in traditional lithium-ion battery negative electrode materials are solved, and higher energy density, longer cycle life and faster charging speed are achieved.

CN119852380APending Publication Date: 2025-04-18JIANGSU ZENIO NEW ENERGY BATTERY TECH CO LTD

Patent Information

Application Number
CN202510317676.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-18
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The specific capacity of the negative electrode material of traditional lithium-ion batteries is low, and lithium dendrites are prone to growth during charging, resulting in reduced safety and unstable performance.

Method used

A composite material composed of porous organic frame material and metal sulfide quantum dots is used as the negative electrode material to form an S-shaped heterojunction structure to enhance electron migration and redox capabilities.

Benefits of technology

It improves the energy density, cycle life and charging speed of lithium-ion batteries, reduces the growth risk of lithium dendrites, and improves the overall performance and safety of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119852380A_ABST
    Figure CN119852380A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of batteries, in particular to a negative electrode material, a preparation method thereof and a battery. The negative electrode material provided by the invention comprises a porous organic framework material and metal sulfide quantum dots. Wherein the porous organic framework material has a relatively large specific surface area and rich active sites, so that the metal sulfide quantum dots can be anchored, the agglomeration of the metal sulfide quantum dots is avoided, and after the porous organic framework material and the metal sulfide quantum dots form an S-shaped heterojunction structure, the energy band structure of the porous organic framework material is changed; therefore, the electron migration and oxidation-reduction capabilities are enhanced, and the electrochemical reaction kinetics is remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a negative electrode material and a preparation method thereof, and a battery. Background Art

[0002] With the continuous advancement of science and technology and the urgent global demand for clean energy, lithium-ion batteries, as important energy storage devices, have great significance for meeting the growing energy demand by improving their performance. As a key component of lithium-ion batteries, negative electrode materials play a vital role in the overall performance of batteries, such as energy density, power density, cycle life and safety performance. Therefore, the research on lithium battery negative electrode materials not only helps to improve battery performance, but also reduces production costs and promotes technological progress in related fields such as electric vehicles, wearable devices, aerospace and space military. Traditional lithium-ion battery negative electrode materials are mainly carbon materials, especially graphite, which is widely used due to its high conductivity, good layered structure and reversibility of lithium ion insertion / extraction. However, the theoretical specific capacity of carbon materials is relatively low (for example, the theoretical specific capacity of graphite is 372 mAh / g), which is far behind the high specific capacity of metallic lithium (3860 mAh / g). In addition, the carbon negative electrode is prone to the growth of lithium dendrites during charging, which not only reduces the safety of the battery, but also may cause serious consequences such as short circuit, thermal runaway and even explosion.

[0003] Therefore, providing a new negative electrode material with higher specific capacity, better cycle stability and safety has become a technical problem that current technicians are eager to solve. Summary of the invention

[0004] In view of this, the present invention aims to solve one of the technical problems in the related art at least to a certain extent. To this end, the present invention provides a negative electrode material and a preparation method thereof and a battery, wherein the negative electrode material has higher specific capacity, better cycle stability and safety.

[0005] In order to solve the above technical problems, this application is implemented as follows: According to one aspect of the present application, an embodiment of the present application provides a negative electrode material, the negative electrode material comprising: a composite material composed of a porous organic framework material and metal sulfide quantum dots; Wherein, the porous organic framework material and the metal sulfide quantum dots form an S-type heterojunction structure; The porous organic framework material includes at least one of a covalent organic framework material and a metal-composite covalent organic framework material.

[0006] In addition, the diaphragm according to the present application may also have the following additional technical features: In some embodiments, the covalent organic framework material includes at least one of a tetrathiafulvalene-based covalent organic framework material, a thiol-based covalent organic framework material, a thiol-based covalent organic framework material, and a thiol-based covalent organic framework material.

[0007] Preferably, the covalent organic framework material comprises a tetrathiafulvalene-based covalent organic framework material.

[0008] In some of the embodiments, the metal in the metal-composite covalent organic framework material includes at least one of Zn, Cd, Mn, Cu, Ni, Pb, Pt or Au; Preferably, the metal in the metal-composite covalent organic framework material includes Zn.

[0009] In some of the embodiments, the metal sulfide quantum dots include at least one of ZnCdS, MnCdS, FeCdS, CoCdS or ZnInS; Preferably, the metal sulfide quantum dots include ZnCdS.

[0010] In some of the embodiments, the mass ratio of the porous organic framework material to the metal sulfide quantum dots is (1-9): (9-1); Preferably, the mass ratio of the porous organic framework material to the metal sulfide quantum dots is 6:4.

[0011] According to another aspect of the present application, an embodiment of the present application provides a method for preparing a negative electrode material, comprising the following steps: The suspension of the porous organic framework material and the suspension of the metal sulfide quantum dots are mixed, and after separation and drying, a negative electrode material is obtained; The porous organic framework material includes at least one of a covalent organic framework material and a metal-composite covalent organic framework material; the porous organic framework material and the metal sulfide quantum dots form an S-type heterojunction structure.

[0012] In some of the embodiments, the mixing of the suspension of the porous organic framework material and the suspension of the metal sulfide quantum dots is performed by dropping the suspension of the porous organic framework material into the suspension of the metal sulfide quantum dots, or by dropping the suspension of the metal sulfide quantum dots into a drop of a suspension of the porous organic framework material.

[0013] In some embodiments, the mixing of the suspension of the porous organic framework material and the suspension of the metal sulfide quantum dots comprises a stirring step.

[0014] In some embodiments, the stirring temperature is 50-70° C., and the stirring time is 5-7 hours.

[0015] In some embodiments, the separation is performed by centrifugation.

[0016] In some embodiments, the centrifugal speed is 6000-8000 r / min, and the centrifugal time is 30-60 min.

[0017] In some embodiments, the drying temperature is 50-70° C., and the drying time is 12-20 hours.

[0018] In some of the embodiments, the mass ratio of the porous organic framework material to the metal sulfide quantum dots is (1-9): (9-1); Preferably, the mass ratio of the porous organic framework material to the metal sulfide quantum dots is 6:4.

[0019] In some embodiments, the method for preparing the covalent organic framework material comprises: Mixing a covalent organic framework material source and a structure directing agent in a solvent A to obtain a suspension; A pH regulator is added to the suspension to adjust the pH value, a freeze-thaw cycle treatment is performed, and then drying is performed to obtain a covalent organic framework material.

[0020] In some embodiments, the molar ratio of the covalent organic framework material source to the structure directing agent is (1-3): (0.5-1.5).

[0021] In some embodiments, the solvent A includes a first solvent and a second solvent; the first solvent includes at least one of o-dichlorobenzene, toluene, xylene or chloroform; the second solvent includes at least one of ethanol, methanol, propanol or butanol; and the volume ratio of the first solvent to the second solvent is (2~4):(6~8).

[0022] In some embodiments, the structure directing agent includes at least one of tetraphenyl-p-phenylenediamine, aniline, benzidine, sodium dodecyl sulfate, hexadecyltrimethylammonium bromide, polyvinylpyrrolidone or polystyrene.

[0023] In some embodiments, the pH value is adjusted to 8.5-9.5.

[0024] In some embodiments, the freeze-thaw cycle is repeated 1 to 3 times.

[0025] In some embodiments, the freezing temperature is -60 to -80°C, and the freezing time is 30 to 60 minutes.

[0026] In some embodiments, the drying temperature is 110-120° C., and the drying time is 2-4 days.

[0027] In some embodiments, the method for preparing the metal composite covalent organic framework material comprises: Mixing a covalent organic framework material source, a structure directing agent and a metal powder in a solvent B to obtain a suspension; A pH regulator is added to the suspension to adjust the pH value, and a freeze-thaw cycle treatment is performed, followed by drying to obtain a metal-complexed covalent organic framework material.

[0028] In some embodiments, the molar ratio of the covalent organic framework material source, the structure directing agent and the metal powder is (1-3): (0.5-1.5): (0.5-1.5).

[0029] In some embodiments, the solvent B includes a third solvent and a fourth solvent; the third solvent includes at least one of o-dichlorobenzene, toluene, xylene or chloroform; the fourth solvent includes at least one of ethanol, methanol, propanol or butanol; and the volume ratio of the third solvent to the fourth solvent is (2~4):(6~8).

[0030] In some embodiments, the structure directing agent includes at least one of tetraphenyl-p-phenylenediamine, aniline, benzidine, sodium dodecyl sulfate, hexadecyltrimethylammonium bromide, polyvinylpyrrolidone or polystyrene.

[0031] In some embodiments, the metal in the metal powder includes at least one of Zn, Cd, Mn, Cu, Ni, Pb, Pt or Au.

[0032] In some embodiments, the pH value is adjusted to 8.5-9.5.

[0033] In some embodiments, the freeze-thaw cycle is repeated 1 to 3 times.

[0034] In some embodiments, the freezing temperature is -60 to -80°C, and the freezing time is 30 to 60 minutes.

[0035] In some embodiments, the drying temperature is 110-120° C., and the drying time is 2-4 days.

[0036] In some embodiments, the method for preparing the metal sulfide quantum dots comprises: The metal source A and the metal source B are mixed in a fifth solvent and heated to a first temperature; then a sulfur source is added and heated to a second temperature, and metal sulfide quantum dots are obtained after reaction.

[0037] In some of the embodiments, the metal source A and the metal source B independently include at least one of metal hydrochlorides, metal sulfates, metal nitrates, metal oxides, metal carbonates, metal phosphates, metal borates, metal chromates, and metal molybdates; and the metal includes at least one of Zn, Cd, Mn, Fe, Co, and In.

[0038] In some embodiments, the volume molar ratio of the metal source A, the metal source B and the fifth solvent is (1-3 moL): (1-3 moL): (15-25 L).

[0039] In some embodiments, the molar ratio of the metal source A to the sulfur source is (1-3):2.

[0040] In some embodiments, the first temperature is 150-170°C.

[0041] In some embodiments, the second temperature is 175-190°C.

[0042] In some embodiments, the reaction time is 1 to 3 hours.

[0043] According to another aspect of the present application, an embodiment of the present application provides a battery, including a negative electrode sheet, wherein the negative electrode sheet includes a negative electrode material, and the negative electrode material is the aforementioned negative electrode material or the negative electrode material prepared according to the aforementioned preparation method.

[0044] Implementing the technical solution of the present invention has at least the following beneficial effects: In an embodiment of the present application, the negative electrode material provided includes a porous organic framework material and metal sulfide quantum dots. Among them, the porous organic framework material has a large specific surface area and rich active sites that can anchor metal sulfide quantum dots to prevent the metal sulfide quantum dots from agglomerating. After the porous organic framework material and the metal sulfide quantum dots form an S-type heterojunction structure, the energy band structure of the porous organic framework material changes, thereby enhancing electron migration and redox capabilities, and significantly improving the electrochemical reaction kinetics. That is, the porous organic framework material and the metal sulfide quantum dots construct a negative electrode material with an S-type heterojunction structure, which solves the problem of low specific capacity of traditional lithium battery negative electrode materials and the easy growth of lithium dendrites during charging, and the lithium battery containing the negative electrode material also has the advantages of higher energy density, longer cycle life and faster charging speed.

[0045] Additional aspects and advantages of the present application will be given in part in the following description, and in part will become obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] Figure 1 Shown is a TEM image of the negative electrode material (Zn-TT-COF / ZCSQ-40) prepared in Example 1 of the present invention.

[0047] Figure 2 Shown is a SEM image of the negative electrode material (Zn-TT-COF / ZCSQ-40) prepared in Example 1 of the present invention.

[0048] Figure 3 Shown is a SEM image of the metal zinc composite covalent organic framework material (Zn-TT-COF) prepared in Example 1 of the present invention.

[0049] Figure 4 Shown is a graph of N2 adsorption-desorption curves of the metal zinc composite covalent organic framework material prepared in Example 1 of the present invention.

[0050] Figure 5 Shown is an X-ray diffraction spectrum of the covalent organic framework material (Zn-TT-COF) composite of ZnCdS quantum dots and metal zinc prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0051] The present application is further described below in conjunction with specific embodiments. It should be understood that these embodiments of the present application are only used to illustrate the present application and are not used to limit the scope of the present application.

[0052] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range or the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0053] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0054] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0055] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0056] If there is no special explanation, the "include" and "comprising" mentioned in this application represent open-ended or closed-ended expressions. For example, the "include" and "comprising" may represent that other components not listed may also be included or only the listed components may be included or only the listed components may be included.

[0057] In the related art, the negative electrode materials of lithium ions are mostly carbon materials. However, the carbon negative electrode has the defect of low specific capacity and there is also the problem of lithium dendrite growth during the charging process.

[0058] [Anode material] In view of this, an embodiment of the present application provides a negative electrode material, the negative electrode material comprising: a composite material composed of a porous organic framework material and metal sulfide quantum dots; Among them, the porous organic framework material and metal sulfide quantum dots constitute an S-type heterojunction structure.

[0059] In the present application, the porous organic framework material includes at least one of a covalent organic framework material or a metal-composite covalent organic framework material. The porous organic framework material has a stable crystalline porous structure and flexible assembly characteristics. Its high specific surface area and ordered pore structure can effectively improve the storage capacity and diffusion rate of lithium ions, while the flexible assembly characteristics allow the chemical functionality to be finely controlled, optimize the interaction with lithium ions, and thus comprehensively enhance the energy density, power density, cycle stability and safety of the battery.

[0060] In the present application, metal sulfide quantum dots can store a higher lithium battery capacity due to their adjustable electronic properties, quantum confinement effect and large specific surface area. Through their unique electronic structure and surface properties, the embedding and extraction process of lithium ions is accelerated, and the charge and discharge rate of the battery is improved. The small size effect of quantum dots helps to alleviate the volume change caused by the embedding and extraction of lithium ions, thereby reducing the structural damage of the negative electrode material and improving the cycle life of the battery. In addition, metal sulfide quantum dots exhibit certain catalytic activity, promote the electrochemical reaction on the surface of the lithium battery negative electrode, and improve the overall performance of the battery.

[0061] In the present application, the porous organic framework material and metal sulfide quantum dots in the negative electrode material can form an S-type heterojunction structure, which combines the high specific surface area and ordered pore structure of the porous organic framework material, and also utilizes the unique quantum confinement effect and excellent photoelectric properties of the metal sulfide quantum dots. The formation of the S-type heterojunction structure promotes the effective separation and transmission between the porous organic framework material and the metal sulfide quantum dot interface, reduces the composite loss, and thus significantly improves the energy conversion efficiency and charge and discharge performance of lithium batteries. Specifically, the S-type heterojunction structure can accelerate the embedding and extraction process of lithium ions at the electrode interface and improve the fast charging capability; at the same time, by optimizing the electron transmission path, the internal resistance of the battery is reduced and the power output is improved. In this way, the common shortcomings of lithium batteries, such as energy loss, limited cycle life, and insufficient fast charging performance, can be solved.

[0062] In more detail, the mechanism of the S-type heterojunction structure formed by porous organic framework materials and metal sulfide quantum dots is: 1. Band matching: Porous organic framework materials and metal sulfide quantum dots have different band structures. When constructing a heterojunction, their bands will be rearranged to adapt to each other's Fermi levels. This band rearrangement is the basis for the formation of an S-type heterojunction.

[0063] 2. Built-in electric field: When the porous organic framework material and the metal sulfide quantum dots come into contact, a built-in electric field will be formed at the interface due to the different work functions.

[0064] 3. Band bending: Under the action of the built-in electric field, the energy bands of the porous organic framework material and the metal sulfide quantum dots are bent, which further promotes the separation of electrons generated by the porous organic framework material and holes generated by the metal sulfide quantum dots and prevents recombination.

[0065] Therefore, in the negative electrode material provided by the present application, the porous organic framework material has a large specific surface area and abundant active sites, which can anchor metal sulfide quantum dots and prevent the metal sulfide quantum dots from agglomerating. After forming an S-type heterojunction structure, the energy band structure of the porous organic framework material changes, thereby enhancing electron migration and redox capabilities, and significantly improving the electrochemical reaction kinetics.

[0066] The term "covalent organic framework materials", referred to as COFs, is a class of porous crystalline materials formed by light elements (such as carbon, hydrogen, oxygen, nitrogen, boron, etc.) connected by strong covalent bonds. They have highly ordered pore structures, large specific surface areas and tunable chemical functions.

[0067] The term "metal-complexed covalent organic frameworks", abbreviated as M-COFs, refers to a class of functionalized materials formed by introducing metal elements or metal complexes into the COFs structure to enhance the physicochemical properties of COFs.

[0068] The term "metal sulfide quantum dots", referred to as QDs, is a class of semiconductor nanomaterials composed of metal and sulfur atoms, and their size is usually between 1-10 nanometers. Because their size is smaller than or close to the exciton Bohr radius, they exhibit discrete energy level structures and unique optical and electrical properties, such as strong fluorescence emission, wide absorption spectrum, wide excitation spectrum but narrow emission spectrum, and tunable emission wavelength.

[0069] In some specific embodiments, the covalent organic framework material includes, but is not limited to, at least one of a tetrathiafulvalene-based covalent organic framework material, a thiol-based covalent organic framework material, a thiol-based covalent organic framework material, and a thiol-based covalent organic framework material.

[0070] Preferably, the covalent organic framework material is selected from tetrathiafulvalene-based covalent organic framework materials. The tetrathiafulvalene groups have good electron transport capabilities, and the covalent bonds between the tetrathiafulvalene groups are stable, so that the tetrathiafulvalene-based covalent organic framework materials have high structural stability and chemical stability.

[0071] In some specific embodiments, the metal in the metal-composite covalent organic framework material includes, but is not limited to, at least one of Zn, Cd, Mn, Cu, Ni, Pb, Pt or Au. The metal in the metal-composite covalent organic framework material has a certain catalytic activity in chemical reactions, which can improve the catalytic performance of the covalent organic framework material; these metal elements form coordination bonds with the coordination groups (carboxyl, hydroxyl, amide, etc.) in the covalent organic framework to enhance the stability and mechanical properties of the composite material. In addition, the metal also promotes the electrochemical reaction on the surface of the lithium battery negative electrode. The metal-composite covalent organic framework material optimizes the transmission path of lithium ions on the negative electrode surface by providing abundant catalytic active sites, reduces the reaction energy barrier, and thus accelerates the insertion and extraction process of lithium ions.

[0072] Preferably, the metal in the metal-composite covalent organic framework material is selected from Zn. First, Zn is cheap and easy to obtain. Second, the catalytic activity is moderate, not too high to make the reaction difficult to control, and not too low to make the catalytic effect poor. Third, the Zn-composite covalent organic framework material (such as the Zn-composite tetrathiofulvalene-based covalent organic framework material) has an ordered conjugated porous structure, a large specific surface area, and abundant adjustable active sites. The fully ordered conjugated structure helps to produce high electron mobility, and the large specific surface area is conducive to Li + The adsorption and diffusion of Li + transmission.

[0073] In some specific embodiments, the metal sulfide quantum dots include at least one of ZnCdS, MnCdS, FeCdS, CoCdS or ZnInS. As an example, the metal sulfide quantum dots can be ZnCdS, MnCdS or FeCdS. Preferably, the metal sulfide quantum dots are selected from ZnCdS, and the metal sulfide quantum dots ZnCdS can remain stable in a variety of chemical environments and are not prone to decomposition or agglomeration.

[0074] Metal sulfide quantum dots have unique electronic structures and surface properties. The unique electronic structure refers to the following: the quantum dots are small in size, and the movement of electrons and holes in them is restricted, which causes changes in the energy level structure of the quantum dots and produces a quantum confinement effect, making the quantum dots have higher electron mobility and lower energy level intervals, thereby improving their electrochemical performance; the surface properties refer to the following: the quantum dots are tiny in size and have an extremely high specific surface area; the surface of the quantum dots can interact with the conductive agent to form a stable interface, reducing the interface resistance.

[0075] In some specific embodiments, the mass ratio of the porous organic framework material and the metal sulfide quantum dots is (1~9): (9~1). As an example, the mass ratio of the porous organic framework material and the metal sulfide quantum dots can be any point value of 1:9, 2:7, 3:8, 4:5, 9:1 or a range value between any two of them. Among them, if the proportion of the porous organic framework material is too large, the excessive porous organic framework material cannot be evenly dispersed among the metal sulfide quantum dots, resulting in agglomeration formation, affecting the uniformity and stability of the composite material; if the content of the porous organic framework material is too small, the porous organic framework material may not be effectively compounded with the metal sulfide quantum dots, resulting in no obvious improvement in the performance of the composite material. The porous organic framework material itself plays a role in stabilizing the metal sulfide quantum dots. If the content of the porous organic framework material is insufficient, the stability of the metal sulfide quantum dots decreases.

[0076] Preferably, the mass ratio of the porous organic framework material to the metal sulfide quantum dots is 6:4.

[0077] Thus, based on the above scheme, a negative electrode material is provided, including a porous organic framework material and metal sulfide quantum dots. Among them, the porous organic framework material has a large specific surface area and abundant active sites that can anchor metal sulfide quantum dots to prevent the metal sulfide quantum dots from agglomerating. After the porous organic framework material and the metal sulfide quantum dots form an S-type heterojunction structure, the energy band structure of the porous organic framework material changes, thereby enhancing electron migration and redox capabilities, and significantly improving the electrochemical reaction kinetics. That is, the porous organic framework material and the metal sulfide quantum dots construct a negative electrode material with an S-type heterojunction structure, which solves the problem of low specific capacity and easy lithium dendrite growth in the charging process of traditional lithium battery negative electrode materials, and the lithium battery containing the negative electrode material also has the advantages of higher energy density, longer cycle life and faster charging speed.

[0078] [Method for preparing negative electrode material] Based on the same inventive concept, the present application embodiment provides a method for preparing a negative electrode material, comprising the following steps: The suspension of the porous organic framework material and the suspension of the metal sulfide quantum dots are mixed, and after separation and drying, a negative electrode material is obtained; The porous organic framework material includes at least one of a covalent organic framework material and a metal-composite covalent organic framework material; the porous organic framework material and the metal sulfide quantum dots form an S-type heterojunction structure.

[0079] It should be understood that all the features and advantages described above for the “negative electrode material” are also applicable to the “method for preparing the negative electrode material” and will not be described in detail here.

[0080] In some specific embodiments, the mixing of the porous organic framework material suspension and the metal sulfide quantum dot suspension is performed by adding the porous organic framework material suspension dropwise to the metal sulfide quantum dot suspension, or adding the metal sulfide quantum dot suspension to the porous organic framework material suspension dropwise.

[0081] In some specific embodiments, the dripping rate is 1 to 3 drops / second. As an example, the dripping rate can be 1 drop / second, 2 drops / second, or 3 drops / second. Mixing the suspension of the porous organic framework material and the suspension of the metal sulfide quantum dots by dripping can avoid adding a large amount of a certain suspension at one time, resulting in excessive local concentration, thereby generating agglomeration or precipitation, and can also prevent agglomeration caused by too fast a reaction speed, thereby forming a more uniform composite material.

[0082] In some specific embodiments, mixing the suspension of the porous organic framework material and the suspension of the metal sulfide quantum dots comprises a stirring step.

[0083] In some specific embodiments, the stirring temperature is 50-70°C, and the stirring time is 5-7h. As an example, the stirring temperature can be any one of 50°C, 60°C, and 70°C, or a range between any two of them. As an example, the stirring time can be any one of 5 h, 6 h, and 7 h, or a range between any two of them.

[0084] In some embodiments, separation is performed by centrifugation.

[0085] In some specific embodiments, the centrifugal speed is 6000-8000 r / min, and the centrifugal time is 30-60 min. As an example, the centrifugal speed can be any one of 6000 r / min, 7000 r / min, 8000 r / min, or a range between any two of them. As an example, the centrifugal time can be any one of 30 min, 40 min, 50 min, 60 min, or a range between any two of them.

[0086] In some specific embodiments, after the centrifugation, a washing step is further included, and the detergent includes at least one of water and ethanol. As an example, the detergent can be water or ethanol.

[0087] In some specific embodiments, the drying temperature is 50-70°C, and the drying time is 12-20 hours. As an example, the drying temperature can be any one of 50°C, 60°C, 70°C, or a range between any two of them. As an example, the drying time can be any one of 12h, 14h, 16h, 18h, 20h, or a range between any two of them.

[0088] In some specific embodiments, the mass ratio of the porous organic framework material and the metal sulfide quantum dots is (1~9): (9~1). As an example, the mass ratio of the porous organic framework material and the metal sulfide quantum dots can be any one of 1:9, 2:7, 3:8, 4:5, 9:1 or a range of values ​​between any two of them. Among them, if the proportion of the porous organic framework material is too large, the excessive porous organic framework material cannot be evenly dispersed among the metal sulfide quantum dots, resulting in agglomeration formation, affecting the uniformity and stability of the composite material; if the content of the porous organic framework material is too small, the porous organic framework material may not be able to effectively compound with the metal sulfide quantum dots, resulting in an insignificant improvement in the performance of the composite material. The porous organic framework material itself plays a role in stabilizing the metal sulfide quantum dots. If the content of the porous organic framework material is insufficient, the stability of the metal sulfide quantum dots decreases.

[0089] Preferably, the mass ratio of the porous organic framework material to the metal sulfide quantum dots is 6:4.

[0090] [Preparation of covalent organic framework materials] In some specific embodiments, the method for preparing the covalent organic framework material comprises: Mixing a covalent organic framework material source and a structure directing agent in a solvent A to obtain a suspension; A pH regulator is added to the suspension to adjust the pH value, a freeze-thaw cycle treatment is performed, and then heating is performed to obtain a covalent organic framework material.

[0091] In some specific embodiments, the molar ratio of the covalent organic framework material source to the structure directing agent is (1-3): (0.5-1.5). As an example, the molar ratio of the covalent organic framework material source to the structure directing agent can be any one of 1:0.5, 1:1.5, 1:1, 2:0.5, 3:1, or a range between any two of them.

[0092] In some embodiments, solvent A includes a first solvent and a second solvent. In some embodiments, the first solvent includes, but is not limited to, at least one of o-dichlorobenzene, toluene, xylene, or chloroform. The first solvent is an organic solvent that can decompose organic solid powder and control the product morphology.

[0093] It should be noted that there is no limitation on the type of the first solvent, as long as it can decompose the organic solid powder and control the morphology of the product.

[0094] In some embodiments, the second solvent includes, but is not limited to, at least one of ethanol, methanol, propanol, or butanol. The second solvent can control the evaporation rate of the reaction system and adjust the polarity of the reaction system.

[0095] It should be noted that the type of the second solvent is not limited, as long as it can control the evaporation rate of the reaction system and adjust the polarity of the reaction system.

[0096] In some specific embodiments, the volume ratio of the first solvent to the second solvent is (2-4):(6-8). As an example, the volume ratio of the first solvent to the second solvent can be any one of 2:6, 3:7, 4:8 or a range between any two of them.

[0097] In some specific embodiments, the structure directing agent includes, but is not limited to, at least one of tetraphenyl-p-phenylenediamine, aniline, benzidine, sodium dodecyl sulfate, hexadecyltrimethylammonium bromide, polyvinylpyrrolidone, or polystyrene. As an example, the structure directing agent can be tetraphenyl-p-phenylenediamine, aniline, or benzidine.

[0098] In some specific embodiments, the method of mixing the covalent organic framework material source and the structure directing agent in the solvent includes, but is not limited to, ultrasound. The ultrasound time is not limited here, and it can be until a uniform and stable suspension is obtained.

[0099] In some embodiments, the pH value is adjusted to 8.5-9.5. As an example, the pH value is adjusted to any one of 8.5, 9, 9.5 or a range between any two of them.

[0100] In some specific embodiments, the pH regulator includes, but is not limited to, at least one of trifluoroacetic acid, formic acid, acetic acid, phosphoric acid, citric acid or lactic acid. Preferably, the pH regulator is selected from trifluoroacetic acid, which has extremely strong acidity and can quickly and effectively adjust the pH of the solution to a range suitable for the synthesis of covalent organic framework materials, providing the necessary acidic environment for chemical reactions; trifluoroacetic acid can also have a certain catalytic effect on the reaction process, promote the interaction between reactants and the formation of covalent bonds, thereby accelerating the synthesis of covalent organic framework materials; trifluoroacetic acid is relatively stable, not easy to decompose or produce by-products, and helps to ensure the purity and consistency of the synthesis of covalent organic framework materials.

[0101] In some embodiments, the freeze-thaw cycle is repeated 1 to 3 times. As an example, the number of freeze cycles can be 1, 2, or 3. Continuous freeze-thaw cycle treatment (which can promote molecular rearrangement) can promote structural rearrangement and possible chemical reactions. Too many cycles can lead to material degradation or structural damage.

[0102] In some specific embodiments, the freezing temperature is -60 to -80°C, and the freezing time is 30 to 60 minutes. As an example, the freezing temperature can be any point value of -60°C, -70°C, -80°C, or a range value between any two of them. As an example, the freezing time can be any point value of 30 minutes, 40 minutes, 50 minutes, 60 minutes, or a range value between any two of them. It should be noted that if the freezing temperature is lower, it corresponds to a shorter freezing time.

[0103] In some specific embodiments, the thawing method includes, but is not limited to, heating thawing, and the temperature of heating thawing is 60-80° C. As an example, the temperature of heating thawing can be any one of 60° C., 70° C., and 80° C., or a range between any two of them.

[0104] In some specific embodiments, the drying is performed under closed conditions to prevent any exchange of gas or liquid, and the formation of the covalent organic framework material can be promoted during the drying process.

[0105] In some specific embodiments, the drying temperature is 110-120° C., and the drying time is 2-4 days. As an example, the drying temperature can be any one of 110° C., 115° C., 120° C., or a range between any two of them. As an example, the drying time can be any one of 2 days, 3 days, 4 days, or a range between any two of them.

[0106] In some specific embodiments, a washing step is further included after drying, and the product needs to be cooled to room temperature before washing. The unreacted reactants and their by-products can be removed by washing.

[0107] In some embodiments, the detergent includes, but is not limited to, at least one of acetone, dichloromethane, tetrahydrofuran, isopropanol, acetonitrile, methanol, or toluene.

[0108] In some specific embodiments, after washing, the precipitate obtained by centrifugation is the covalent organic framework material.

[0109] [Preparation of metal-complex covalent organic framework materials] In some specific embodiments, the method for preparing a metal-complex covalent organic framework material comprises: Mixing a covalent organic framework material source, a structure directing agent and a metal powder in a solvent B to obtain a suspension; A pH regulator is added to the suspension to adjust the pH value, and a freeze-thaw cycle treatment is performed, followed by drying to obtain a metal-complexed covalent organic framework material.

[0110] In some specific embodiments, the molar ratio of the covalent organic framework material source, the structure directing agent and the metal powder is (1-3): (0.5-1.5): (0.5-1.5). As an example, the molar ratio of the covalent organic framework material source, the structure directing agent and the metal powder can be any one of 1:0.5:0.5, 1:1.5:1.5, 1:1:1, 2:0.5:0.5, 3:1:1, or a range between any two of them.

[0111] In some embodiments, solvent B includes a third solvent and a fourth solvent.

[0112] In some specific embodiments, the third solvent includes, but is not limited to, at least one of o-dichlorobenzene, toluene, xylene, or chloroform. The third solvent is an organic solvent that can decompose organic solid powder and control the morphology of the product.

[0113] It should be noted that there is no limitation on the type of the third solvent, as long as it can decompose the organic solid powder and control the morphology of the product.

[0114] In some embodiments, the fourth solvent includes, but is not limited to, at least one of ethanol, methanol, propanol, or butanol. The fourth solvent can control the evaporation rate of the reaction system and adjust the polarity of the reaction system.

[0115] It should be noted that the type of the fourth solvent is not limited, as long as it can control the evaporation rate of the reaction system and adjust the polarity of the reaction system.

[0116] In some specific embodiments, the volume ratio of the third solvent to the fourth solvent is (2-4):(6-8). As an example, the volume ratio of the third solvent to the fourth solvent can be any one of 2:6, 3:7, 4:8 or a range between any two of them.

[0117] In some specific embodiments, the structure directing agent includes, but is not limited to, at least one of tetraphenyl-p-phenylenediamine, aniline, benzidine, sodium dodecyl sulfate, hexadecyltrimethylammonium bromide, polyvinylpyrrolidone, or polystyrene. As an example, the structure directing agent can be tetraphenyl-p-phenylenediamine, aniline, or benzidine.

[0118] In some specific embodiments, the method of mixing the covalent organic framework material source, the structure directing agent and the metal powder in the solvent includes, but is not limited to, ultrasound. The ultrasound time is not limited here, until a uniform and stable suspension is obtained.

[0119] In some embodiments, the pH value is adjusted to 8.5-9.5. As an example, the pH value is adjusted to any one of 8.5, 9, 9.5 or a range between any two of them.

[0120] In some specific embodiments, the pH regulator includes, but is not limited to, at least one of trifluoroacetic acid, formic acid, acetic acid, phosphoric acid, citric acid or lactic acid. Preferably, the pH regulator is selected from trifluoroacetic acid, which has extremely strong acidity and can quickly and effectively adjust the pH of the solution to a range suitable for the synthesis of covalent organic framework materials, providing the necessary acidic environment for chemical reactions; trifluoroacetic acid can also have a certain catalytic effect on the reaction process, promote the interaction between reactants and the formation of covalent bonds, thereby accelerating the synthesis of covalent organic framework materials; trifluoroacetic acid is relatively stable, not easy to decompose or produce by-products, and helps to ensure the purity and consistency of the synthesis of covalent organic framework materials.

[0121] In some embodiments, the freeze-thaw cycle is repeated 1 to 3 times. As an example, the number of freeze cycles can be 1, 2, or 3. Continuous freeze-thaw cycle treatment (which can promote molecular rearrangement) can promote structural rearrangement and possible chemical reactions. Too many cycles can lead to material degradation or structural damage.

[0122] In some specific embodiments, the freezing temperature is -60 to -80°C, and the freezing time is 30 to 60 minutes. As an example, the freezing temperature can be any point value of -60°C, -70°C, -80°C, or a range value between any two of them. As an example, the freezing time can be any point value of 30 minutes, 40 minutes, 50 minutes, 60 minutes, or a range value between any two of them. It should be noted that if the freezing temperature is lower, it corresponds to a shorter freezing time.

[0123] In some specific embodiments, the thawing method includes, but is not limited to, heating thawing, and the temperature of heating thawing is 60-80° C. As an example, the temperature of heating thawing can be any one of 60° C., 70° C., and 80° C., or a range between any two of them.

[0124] In some specific embodiments, the drying is performed under closed conditions to prevent any exchange of gas or liquid, and the formation of the covalent organic framework material can be promoted during the drying process.

[0125] In some specific embodiments, the drying temperature is 110-120° C., and the drying time is 2-4 days. As an example, the drying temperature can be any one of 110° C., 115° C., 120° C., or a range between any two of them. As an example, the drying time can be any one of 2 days, 3 days, 4 days, or a range between any two of them.

[0126] In some specific embodiments, a washing step is further included after drying, and the product needs to be cooled to room temperature before washing. The unreacted reactants and their by-products can be removed by washing.

[0127] In some embodiments, the detergent includes, but is not limited to, at least one of acetone, dichloromethane, tetrahydrofuran, isopropanol, acetonitrile, methanol, or toluene.

[0128] In some specific embodiments, after washing, the precipitate obtained by centrifugation is the metal-complexed covalent organic framework material.

[0129] [Preparation of Metal Sulfide Quantum Dots] In some specific embodiments, the method for preparing metal sulfide quantum dots comprises: The metal source A and the metal source B are mixed in a fifth solvent and heated to a first temperature; then a sulfur source is added and heated to a second temperature, and metal sulfide quantum dots are obtained after reaction.

[0130] In some specific embodiments, metal source A and metal source B each independently include at least one of metal hydrochlorides, metal sulfates, metal nitrates, metal oxides, metal carbonates, metal phosphates, metal borates, metal chromates, and metal molybdates.

[0131] In some specific embodiments, the metal includes at least one of Zn, Cd, Mn, Fe, Co, and In. As an example, the metal may be Zn, Cd, or Mn.

[0132] In some specific embodiments, metal source A and metal source B are selected from one of metal hydrochlorides, metal sulfates, metal nitrates, metal oxides, metal carbonates, metal phosphates, metal borates, metal chromates, and metal molybdates corresponding to the two metals. As an example, when preparing ZnCdS, metal source A can be zinc chloride, and metal source B can be chromium chloride. Among them, zinc chloride has the advantages of good solubility, controllability, purity and stability, and economy; cadmium ions in cadmium chloride have the advantages of high reactivity, low cost, good solubility, and relative safety.

[0133] In some specific embodiments, the volume molar ratio of the metal source A, the metal source B and the fifth solvent is (1-3 moL): (1-3 moL): (15-25 L). As an example, the volume molar ratio of the metal source A, the metal source B and the solvent can be any one of 1 moL: 1 moL: 15 L, 2 moL: 2 moL: 18 L, 3 moL: 3 moL: 25 L, or a range between any two of them.

[0134] In some specific embodiments, the molar ratio of the metal source A to the sulfur source is (1-3): 2. As an example, the molar ratio of the metal source A to the sulfur source can be any one of 1:2, 2:2, 3:2 or a range between any two of them.

[0135] In some specific embodiments, the fifth solvent includes, but is not limited to, at least one of ethylene glycol, dimethyl sulfoxide, NN-dimethylformamide, glycerol, or ethanol. As an example, the fifth solvent may be ethylene glycol or ethanol.

[0136] In some specific embodiments, the first temperature is 150-170° C. As an example, the first temperature can be any one of 150° C., 160° C., 170° C., or any range between the two. Heating to this temperature range can ensure that the salt is completely dissolved or initiate a preliminary chemical reaction.

[0137] In some specific embodiments, the second temperature is 175-190° C. As an example, the second reaction temperature can be any one of 170° C., 180° C., 190° C., or a range of values ​​between any two of them. This temperature setting is intended to promote the reaction between the metal ions of the metal source A, the metal ions of the metal source B, and the S²⁻ ions of the sulfur source to form ZnCdS nanoparticles.

[0138] In some specific embodiments, the reaction time is 1 to 3 hours. As an example, the reaction time can be any one of 1 hour, 2 hours, and 3 hours, or a range between any two of them.

[0139] In some specific embodiments, the reaction further includes washing and drying steps. After the reaction is completed, water and ethanol are used for washing in sequence to remove unreacted raw materials, by-products and residual solvents thereof; and drying is performed by placing the mixture at room temperature for more than 12 hours until the residual water and solvent are completely removed.

[0140] Thus, based on the above, the present invention first prepares porous organic framework materials and metal sulfide quantum dots, and then mixes them in the form of porous organic framework material suspension and metal sulfide quantum dot suspension respectively to obtain negative electrode materials. The porous organic framework material in the negative electrode material has a large specific surface area and rich active sites that can anchor metal sulfide quantum dots, avoid metal sulfide quantum dots from agglomerating, and form an S-type heterojunction structure. The energy band structure of the porous organic framework material changes, thereby enhancing electron migration and redox ability, and significantly improving electrochemical reaction kinetics. That is, the porous organic framework material and the metal sulfide quantum dots construct a negative electrode material with an S-type heterojunction structure, which solves the problem of low specific capacity of traditional lithium battery negative electrode materials and the problem of lithium dendrite growth that is prone to occur during charging, and the lithium battery containing the negative electrode material also has the advantages of higher energy density, longer cycle life and faster charging speed. In addition, the preparation method of the negative electrode material provided in the present application is relatively simple and can be widely promoted and applied.

[0141] Based on the same inventive concept, an embodiment of the present application provides a battery, including a negative electrode sheet, wherein the negative electrode sheet includes a negative electrode material, and the negative electrode material is the aforementioned negative electrode material or the negative electrode material prepared according to the aforementioned preparation method.

[0142] [Negative electrode sheet preparation] The negative electrode material, binder and conductive agent are mixed and ground, and then water is added to obtain slurry. The slurry is coated on the current collector and dried to obtain the negative electrode sheet.

[0143] In some embodiments, the mass ratio of the negative electrode material, the binder, and the conductive agent is (6-8): (1-3): (0.5-1.5). As an example, the mass ratio of the negative electrode material, the binder, and the conductive agent can be any one of 6:1:0.5, 7:2:1, 8:3:1.5, or a range between any two of them.

[0144] In some embodiments, the particle size of the negative electrode material, the binder, and the conductive agent after grinding is 10 nm to 100 nm. As an example, the particle size of the negative electrode material, the binder, and the conductive agent after grinding can be any one of 10 nm, 30 nm, 50 nm, 70 nm, 90 nm, and 100 nm, or a range between any two of them.

[0145] In some embodiments, the current collector includes at least one of copper foil, nickel foam, nickel mesh, or composite copper foil. As an example, the current collector can be copper foil, nickel foam, or the like.

[0146] In some embodiments, the coating thickness of the slurry is 100 μm to 200 μm. As an example, the coating thickness of the slurry can be any one of 100 μm, 120 μm, 140 μm, 160 μm, 180 μm, and 200 μm, or a range between any two of them.

[0147] In some embodiments, drying is performed in a vacuum drying oven, the drying temperature is 70-90°C, and the drying time is 10-15 hours. As an example, the drying temperature can be any one of 70°C, 80°C, 90°C, or a range between any two of them. The drying time can be any one of 10 hours, 12 hours, 14 hours, 15 hours, or a range between any two of them.

[0148] In some embodiments, after the negative electrode sheet is prepared, it can be cut into a desired size by a cutter.

[0149] Since the battery includes a negative electrode plate made of the negative electrode material provided in the embodiment of the present application, it has the advantages of higher energy density, longer cycle life and faster charging speed.

[0150] In some embodiments, the battery may be a lithium-ion battery. The battery stacking type may be, for example, a wound or laminated battery, and the structural type may be, for example, a square shell (aluminum shell, steel shell, etc.) battery, a soft pack battery, or a cylindrical battery, etc., without specific limitation, and the battery has excellent high temperature performance and electrical performance.

[0151] In some embodiments, the battery further comprises a positive electrode sheet, an electrolyte and a separator. That is, the battery comprises a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator.

[0152] In this embodiment, there is no limitation on the materials and structures of the positive electrode sheet, the positive current collector, the conductive agent, the binder in the positive active material layer, and the like, and any positive electrode sheet structure and composition known in the art that can be used for secondary batteries can be selected.

[0153] In this embodiment, the type of the separator is not limited, and any separator known in the art that can be used in secondary batteries can be selected.

[0154] It should also be noted that the battery of the present application is not limited to the specific material or type of the electrolyte, and the components and types that are known in the art and can be used for secondary batteries can be selected as long as the purpose of the present application can be achieved.

[0155] Since the battery provided in the embodiment of the present invention adopts all the technical solutions of the above embodiments, it has at least all the beneficial effects brought by the technical solutions of the above embodiments, which will not be described one by one here.

[0156] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific technology or conditions are specified in the embodiments, the technology or conditions described in the literature in this area or the product instructions are used. If the manufacturer of the reagents, materials or instruments used is not specified, they are all conventional products that can be obtained commercially.

[0157] Example 1 S1: First, add 0.3 mL of o-dichlorobenzene and 0.7 mL of ethanol into a 10 mL glass tube, and then introduce 0.02 mmol of tetrathiafulvalene covalent organic framework material source (TT) powder, 0.01 mmol of tetraphenyl-p-phenylenediamine (TPPDA) powder, and 0.01 mmol of zinc powder into the mixed solvent. To ensure that the solid components are fully dispersed in the solvent, the mixture is placed in an ultrasonic device for 5 min until a uniform and stable suspension is formed.

[0158] S2: Subsequently, 100 μL of trifluoroacetic acid (TFA) was added dropwise to the homogeneous suspension prepared above. After the addition was completed, the suspension was placed in a freezing pump for three consecutive freeze-thaw cycles (freezing temperature -60°C, time 30 min; thawing temperature 60°C, time 30 min) to promote structural rearrangement and possible chemical reactions. Afterwards, the glass tube containing the treatment solution was tightly sealed to prevent any exchange of gas or liquid, and then placed in an oven at 120°C for heating for 3 days to promote the formation of a covalent organic framework material composited with metal zinc.

[0159] S3: After heating, the reaction product is cooled to room temperature and washed with acetone solvent to remove unreacted substances and by-products. After washing, the red precipitate is collected by centrifugation. The precipitate is the synthesized red powder of the metal zinc composite covalent organic framework material, named Zn-TT-COF.

[0160] S4: Dissolve 2 mmol of zinc chloride (ZnCl2) and 2 mmol of cadmium chloride (CdCl2) together in 20 mL of ethylene glycol, and then heat the mixture to 160 °C to ensure that the salts are completely dissolved and to possibly initiate a preliminary chemical reaction.

[0161] S5: Next, 2 mmol of sodium sulfide nonahydrate (Na2S·9H2O) was added to the hot solution and continued to heat to 180 °C. This temperature setting was intended to promote the reaction between Zn²⁺ and Cd²⁺ ions and S²⁻ ions to form ZnCdS nanoparticles. The mixture was stirred for 2 h at 180 °C to ensure that the reaction was fully carried out. After the reaction, the product was washed with deionized water and anhydrous ethanol in turn to remove unreacted precursors, by-products and solvent residues. Finally, the washed product was placed in a centrifuge tube and dried overnight at room temperature to completely remove residual water and solvent to obtain the product ZnCdS quantum dots.

[0162] S6: 60 mg of Zn-TT-COF and 40 mg of ZnCdS were dispersed in 30 mL of methanol and ultrasonicated for 10 min. Then the suspension of Zn-TT-COF was added dropwise to the ZnCdS emulsion dispersion. The mixture was stirred at 60 °C for 6 h, and then the resulting precipitate was centrifuged, washed with water and ethanol, and dried in vacuum at 60 °C overnight to prepare a Zn-TT-COF / ZCSQ composite containing 40 wt% ZnCdS, which was labeled as Zn-TT-COF / ZCSQ-40.

[0163] Example 2 The only difference between Example 2 and Example 1 is that in step S6 of Example 2, the amount of Zn-TT-COF added is 10 mg and the amount of ZnCdS added is 90 mg, and the rest is the same as Example 1. The Zn-TT-COF / ZCSQ composite containing 90 wt% ZnCdS prepared in Example 2 is labeled as Zn-TT-COF / ZCSQ-90.

[0164] Example 3 The only difference between Example 3 and Example 1 is that in step S6 of Example 3, the amount of Zn-TT-COF added is 90 mg and the amount of ZnCdS added is 10 mg, and the rest is the same as Example 1. The Zn-TT-COF / ZCSQ composite containing 10 wt% ZnCdS prepared in Example 3 is labeled as Zn-TT-COF / ZCSQ-10.

[0165] Example 4 The only difference between Example 4 and Example 1 is that in step S6 of Example 4, the amount of Zn-TT-COF added is 10 mg and the amount of ZnCdS added is 91 mg, and the rest is the same as Example 1. The Zn-TT-COF / ZCSQ composite containing about 91 wt% ZnCdS prepared in Example 4 is labeled as Zn-TT-COF / ZCSQ-91.

[0166] Example 5 The only difference between Example 5 and Example 1 is that in step S1 of Example 54, TT powder is replaced with sodium hydrosulfide, and the rest is the same as Example 1. The Zn-HS-COF / ZCSQ composite containing 40 wt% ZnCdS prepared in Example 5 is labeled as Zn-HS-COF / ZCSQ-40.

[0167] Example 6 The only difference between Example 6 and Example 1 is that zinc chloride is replaced by manganese chloride in step S4 of Example 6, and the rest is the same as Example 1. The Zn-TT-COF / MCSQ composite containing 40 wt% MnCdS prepared in Example 6 is labeled as Zn-TT-COF / MCSQ-40.

[0168] Example 7 The only difference between Example 7 and Example 1 is that the zinc powder is replaced by nickel powder in step S1 of Example 7, and the rest is the same as Example 1. The Ni-TT-COF / ZCSQ composite containing 40 wt% ZnCdS prepared in Example 7 is labeled as Ni-TT-COF / ZCSQ-40.

[0169] Example 8 The only difference between Example 8 and Example 1 is that no zinc powder is added in step S1 of Example 8, and the rest is the same as Example 1. The TT-COF / ZCSQ composite containing 40 wt% ZnCdS prepared in Example 8 is labeled as TT-COF / ZCSQ-40.

[0170] Example 9 The only difference between Example 9 and Example 1 is that the number of freeze-thaw cycles in step S2 of Example 9 is 2 times.

[0171] Example 10 S1: First, add 0.2 mL of o-dichlorobenzene and 0.6 mL of ethanol into a 10 mL glass tube, and then introduce 0.022 mmol of tetrathiafulvalene covalent organic framework material source (TT) powder, 0.015 mmol of tetraphenyl-p-phenylenediamine (TPPDA) powder, and 0.01 mmol of zinc powder into the mixed solvent. To ensure that the solid components are fully dispersed in the solvent, the mixture is placed in an ultrasonic device for 5 min until a uniform and stable suspension is formed.

[0172] S2: Subsequently, 100 μL of trifluoroacetic acid (TFA) was added dropwise to the homogeneous suspension prepared above. After the addition was completed, the suspension was placed in a freezing pump for three consecutive freeze-thaw cycles (freezing temperature -80°C, time 60 min; thawing temperature 80°C, time 80 min) to promote structural rearrangement and possible chemical reactions. Afterwards, the glass tube containing the treatment solution was tightly sealed to prevent any exchange of gas or liquid, and then placed in an oven at 110°C for 4 days to promote the formation of a covalent organic framework material composited with metal zinc.

[0173] S3: After heating, the reaction product is cooled to room temperature and washed with acetone solvent to remove unreacted substances and by-products. After washing, the red precipitate is collected by centrifugation. The precipitate is the synthesized red powder of the metal zinc composite covalent organic framework material, named Zn-TT-COF.

[0174] S4: Dissolve 1 mmol of zinc chloride (ZnCl2) and 2 mmol of cadmium chloride (CdCl2) together in 20 mL of ethylene glycol, and then heat the mixture to 160 °C to ensure that the salts are completely dissolved and to possibly initiate a preliminary chemical reaction.

[0175] S5: Next, 2 mmol of sodium sulfide nonahydrate (Na2S·9H2O) was added to the hot solution and continued to heat to 185 °C. This temperature setting was intended to promote the reaction between Zn²⁺ and Cd²⁺ ions and S²⁻ ions to form ZnCdS nanoparticles. The mixture was stirred for 1.5 h at 185 °C to ensure that the reaction was fully carried out. After the reaction, the product was washed with deionized water and anhydrous ethanol in turn to remove unreacted precursors, by-products and solvent residues. Finally, the washed product was placed in a centrifuge tube and dried overnight at room temperature to completely remove residual water and solvent to obtain the product ZnCdS quantum dots.

[0176] S6: 50 mg of Zn-TT-COF and 50 mg of ZnCdS were dispersed in 30 mL of methanol and ultrasonicated for 10 min. Then the suspension of Zn-TT-COF was added dropwise to the ZnCdS emulsion dispersion. The mixture was stirred at 63 °C for 6 h, and then the resulting precipitate was centrifuged, washed with water and ethanol, and dried in vacuum at 63 °C overnight to prepare a Zn-TT-COF / ZCSQ composite containing 50 wt% ZnCdS, which was labeled as Zn-TT-COF / ZCSQ-50.

[0177] Comparative Example 1 Comparative Example 1 uses only tetrathiafulvalene-based covalent organic framework material source (TT) powder as the negative electrode material, and the product of Comparative Example 1 is marked as TT.

[0178] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that in Comparative Example 2, the ZnCdS quantum dots prepared by S4 to S5 in Example 1 are used as negative electrode materials, and the product of Comparative Example 2 is marked as ZCSQ.

[0179] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that in Comparative Example 3, Zn-TT-COF prepared by S1 to S3 in Example 1 is used as the negative electrode material, and the product of Comparative Example 3 is marked as Zn-TT-COF.

[0180] Performance Testing 1. Battery preparation The negative electrode materials prepared in each embodiment and comparative example were used as working electrodes, the metal sodium sheet was used as a reference electrode, Whatman GF / D glass fiber was used as a separator, and 1 mol L -1 100 μL of NaPF6 (solvent is diethylene glycol dimethyl ether, commonly known as DIGLYME) was added as the electrolyte. The half-cell was assembled in the order of positive electrode shell, negative electrode material, diaphragm, sodium sheet, gasket, shrapnel and negative electrode shell. The assembled half-cell was clamped on the packaging machine with insulating tweezers for sealing. Finally, the packaged battery was taken out of the glove box and left to stand for 12 hours to allow the electrolyte to fully infiltrate before conducting relevant electrochemical tests.

[0181] 2. Electrochemical performance test First cycle capacity test: Take the sodium ion button half-cells prepared in the embodiment and the comparative example respectively, and test them at 26 °C at 0.1 A g -1 The first cycle capacity test was carried out under the test conditions of current density, charge cut-off voltage of 3.0 V, and discharge cut-off voltage of 0.01 V. The test results of the first cycle discharge specific capacity and the first cycle coulomb efficiency are shown in Table 1.

[0182] 6 A g-1 Cycle life test: Take the sodium ion button half-cells prepared in the embodiment and the comparative example respectively and conduct 6 A g -1 Cyclic test under current density (charge cut-off voltage 3.0 V, discharge cut-off voltage 0.01 V). -1 The test results of the number of cycles when the capacity retention rate drops to 80% under the current density are shown in Table 1.

[0183] Electrochemical impedance spectroscopy test: The electrochemical impedance spectroscopy test of the half-cell was performed using a Letpub electrochemical workstation with a test frequency of 0.01 Hz to 100 kHz. The test results of the charge transfer resistance of the new battery are shown in Table 1.

[0184] Constant current intermittent titration technology test: The sodium ion battery button half-cells prepared in the examples and comparative examples were tested by constant current intermittent titration technology at 26°C using the Xinwei battery testing system (charging cut-off voltage 3.0 V, discharging cut-off voltage 0.01 V). The test results of the sodium ion diffusion coefficient of the new battery are shown in Table 1.

[0185] Table 1 It can be seen from the data in Table 1 that Example 1 has the best performance, which is attributed to the fact that the content of ZnCdS in the Zn-TT-COF / ZCSQ-40 composite is 40 wt%, and this ratio achieves a good balance between the active material ZnCdS and the Zn-TT-COF / ZCSQ matrix. An appropriate amount of ZnCdS not only provides sufficient active sites, but also promotes the effective transmission of electrons and ions. At the same time, the Zn-TT-COF / ZCSQ matrix provides a stable support structure for ZnCdS, which helps to improve the cycle stability of the composite. Therefore, Example 1 exhibits the best first-cycle discharge capacity, first efficiency, number of cycles, as well as relatively low resistance and high ion diffusion coefficient. The performance of Example 2 is relatively poor. This is because the content of ZnCdS in Example 2 is increased to 90 wt%, which causes the distribution of the active material in the composite to be too dense, increasing the resistance to charge transfer and limiting the Li +Diffusion between active sites. Therefore, the first-cycle discharge capacity, first effect, and number of cycles of Example 2 are reduced, while the resistance increases and the ion diffusion coefficient decreases. The content of ZnCdS active material in Example 3 is relatively low (10%), and the support structure and transmission channel provided by the Zn-TT-COF / ZCSQ matrix cannot be fully utilized. Therefore, Example 3 is inferior to Examples 1 and 2 in terms of first-cycle discharge capacity, first effect, and number of cycles. At the same time, due to the low content of ZnCdS, its effect on the resistance and ion diffusion coefficient of the composite may be relatively small. Example 4 exceeds the specified range, and there are too many active materials, which leads to an unstable internal structure of the battery and affects ion transmission; in addition, exceeding the specified range will cause overheating inside the battery and increase the risk of thermal runaway.

[0186] In Example 5, TT powder is replaced with sodium hydrosulfide to explore the effect of different precursors on the performance of the composite material. The experimental results show that the introduction of sodium hydrosulfide has a certain regulatory effect on the structure and electrochemical properties of the composite. Although the interaction mode between sodium hydrosulfide and the Zn-TT-COF / ZCSQ matrix is ​​different from that of TT powder, it provides new active sites for the material and shows potential application value. In Example 6, ZnCdS QDs are replaced with MnCdS QDs to study the optimization potential of different quantum dots on the performance of composite materials. The introduction of MnCdS QDs brings new electronic structure and energy band arrangement characteristics to the material system. Although its charge separation and transmission efficiency are different from those of ZnCdS QDs, it provides a new research direction for further optimizing material performance. In Example 7, Zn powder is replaced with Ni powder to examine the effects of different metal components on the conductivity and chemical stability of the composite material. The introduction of Ni powder provides a new charge transfer path for the material system. Although its conductivity is different from that of Zn powder, it exhibits good structural stability and electrochemical activity, providing new ideas for the multifunctional design of materials. In Example 8, Zn powder was removed to study its effect on the performance of the composite material. The experimental results show that although the removal of Zn powder has a certain effect on the charge transfer efficiency and structural stability, this adjustment provides the possibility of simplified design and cost optimization of the material system. Comparative Example 1 (pure TT) lacks the introduction of active substances such as ZnCdS, so it may show a lower level in electrochemical performance. Comparative Example 2 lacks the support structure and transmission channel provided by the Zn-TT-COF matrix, resulting in electrochemical performance that is not as good as that of the Zn-TT-COF / ZCSQ complex. Although Comparative Example 3 has a stable support structure and transmission channel, it lacks the introduction of active substances such as ZnCdS, so it may show certain limitations in electrochemical performance.

[0187] In addition, the attached Figure 1 and attached Figure 2A large number of evenly distributed tiny particles can be seen, which show obvious characteristics of quantum dots. The size of the quantum dots is uniform and there is no obvious agglomeration, which shows that the growth of quantum dots was successfully controlled during the synthesis process.

[0188] By the attached Figure 3 and attached Figure 4 It can be seen that the specific surface area of ​​Zn-TT-COF is 634.92 m² / g, indicating that Zn-TT-COF has a very rich surface area. At the same time, we also used SEM (attached Figure 3 ) observed the pore size of Zn-TT-COF, and the results showed that the pore size of Zn-TT-COF was 2~5 nm, forming a uniform and ordered pore structure. In other words, Zn-TT-COF has an ordered conjugated porous structure, a large specific surface area, and abundant adjustable active sites. These characteristics together give it excellent Li + Adsorption, diffusion and transport capabilities.

[0189] By the attached Figure 5 According to the attached Figure 5 The X-ray diffraction pattern analysis shows that the diffraction peak position of the ZnCdS sample is highly consistent with the standard PDF card, indicating that its crystal structure is in line with expectations. It is worth noting that in addition to retaining the characteristic diffraction peaks of ZnCdS, the diffraction pattern of the Zn-TT-COF / ZCSQ composite material also shows multiple new diffraction peaks. These additional diffraction peaks can be attributed to the characteristic structure of Zn-TT-COF, and this result confirms the successful preparation of the Zn-TT-COF / ZCSQ composite material.

[0190] Parts of the present invention that are not described in detail are well known to those skilled in the art.

[0191] The basic principle of the present invention is described above in conjunction with specific embodiments. However, it should be pointed out that the advantages, strengths, effects, etc. mentioned in the present invention are only examples and not limitations, and it cannot be considered that these advantages, strengths, effects, etc. must be possessed by each embodiment of the present invention. In addition, the specific details disclosed above are only for the purpose of illustration and facilitation of understanding, rather than limitation, and the above details do not limit the present invention to being implemented by adopting the above specific details.

[0192] It should be noted that the term "and / or" or " / " used in this document is only a description of the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. The singular forms of "a", "the" and "the" used in the embodiments of the present invention and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.

[0193] In the detailed description and claims, a list of items connected by the terms "at least one of," "at least one of," "at least one of," or other similar terms may mean any combination of the listed items. For example, if items A, B are listed, the phrase "at least one of A, B" means only A; only B; or A and B. In another example, if items A, B, C are listed, the phrase "at least one of A, B, C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may include a single element or multiple elements. Item B may include a single element or multiple elements. Item C may include a single element or multiple elements.

[0194] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A negative electrode material, characterized in that: The negative electrode material includes: a composite material composed of a porous organic framework material and metal sulfide quantum dots; Wherein, the porous organic framework material and the metal sulfide quantum dots form an S-type heterojunction structure; The porous organic framework material includes at least one of a covalent organic framework material and a metal-composite covalent organic framework material.

2. The negative electrode material according to claim 1, characterized in that The covalent organic framework material includes at least one of a tetrathiafulvalene-based covalent organic framework material, a thiol-based covalent organic framework material, a thiol-based covalent organic framework material, and a thiol-based covalent organic framework material; And / or, the metal in the metal-composite covalent organic framework material includes at least one of Zn, Cd, Mn, Cu, Ni, Pb, Pt or Au; And / or, the metal sulfide quantum dots include at least one of ZnCdS, MnCdS, FeCdS, CoCdS or ZnInS.

3. The negative electrode material according to any one of claims 1 to 2, characterized in that The mass ratio of the porous organic framework material to the metal sulfide quantum dots is (1-9): (9-1).

4. A method for preparing a negative electrode material, characterized in that: The following steps are involved: The suspension of the porous organic framework material and the suspension of the metal sulfide quantum dots are mixed, and after separation and drying, a negative electrode material is obtained; The porous organic framework material includes at least one of a covalent organic framework material and a metal-composite covalent organic framework material; the porous organic framework material and the metal sulfide quantum dots form an S-type heterojunction structure.

5. The method for preparing the negative electrode material according to claim 4, characterized in that: The preparation method satisfies at least one of the following characteristics (1) to (5): (1) The mixing of the suspension of the porous organic framework material and the suspension of the metal sulfide quantum dots is performed by dropping the suspension of the porous organic framework material into the suspension of the metal sulfide quantum dots, or by dropping the suspension of the metal sulfide quantum dots into the suspension of the porous organic framework material; (2) mixing the suspension of the porous organic framework material and the suspension of the metal sulfide quantum dots includes a stirring step; The stirring temperature is 50-70°C and the stirring time is 5-7h; (3) The separation is carried out by centrifugation; The centrifugal speed is 6000-8000 r / min, and the centrifugal time is 30-60 min; (4) The drying temperature is 50-70°C and the drying time is 12-20 hours; (5) The mass ratio of the porous organic framework material to the metal sulfide quantum dots is (1-9): (9-1).

6. The method for preparing the negative electrode material according to claim 4, characterized in that: The preparation method of the covalent organic framework material comprises: Mixing a covalent organic framework material source and a structure directing agent in a solvent A to obtain a suspension; A pH regulator is added to the suspension to adjust the pH value, a freeze-thaw cycle treatment is performed, and then drying is performed to obtain a covalent organic framework material.

7. The method for preparing the negative electrode material according to claim 6, characterized in that: The method for preparing the covalent organic framework material satisfies at least one of the following characteristics (1) to (7): (1) The molar ratio of the covalent organic framework material source to the structure directing agent is (1-3): (0.5-1.5); (2) The solvent A comprises a first solvent and a second solvent; the first solvent comprises at least one of o-dichlorobenzene, toluene, xylene or chloroform; the second solvent comprises at least one of ethanol, methanol, propanol or butanol; the volume ratio of the first solvent to the second solvent is (2-4):(6-8); (3) the structure directing agent comprises at least one of tetraphenyl-p-phenylenediamine, aniline, benzidine, sodium dodecyl sulfate, hexadecyltrimethylammonium bromide, polyvinylpyrrolidone or polystyrene; (4) adjusting the pH value to 8.5-9.5; (5) the freeze-thaw cycle is repeated 1 to 3 times; (6) The freezing temperature is -60 to -80°C and the freezing time is 30 to 60 minutes; (7) The drying temperature is 110-120°C and the drying time is 2-4 days.

8. The method for preparing the negative electrode material according to claim 4, characterized in that: The preparation method of the metal composite covalent organic framework material comprises: Mixing a covalent organic framework material source, a structure directing agent and a metal powder in a solvent B to obtain a suspension; A pH regulator is added to the suspension to adjust the pH value, and a freeze-thaw cycle treatment is performed, followed by drying to obtain a metal-complexed covalent organic framework material.

9. The method for preparing the negative electrode material according to claim 8, characterized in that: The method for preparing the metal composite covalent organic framework material satisfies at least one of the following characteristics (1) to (8): (1) The molar ratio of the covalent organic framework material source, the structure directing agent and the metal powder is (1-3): (0.5-1.5): (0.5-1.5); (2) The solvent B includes a third solvent and a fourth solvent; the third solvent includes at least one of o-dichlorobenzene, toluene, xylene or chloroform; the fourth solvent includes at least one of ethanol, methanol, propanol or butanol; the volume ratio of the third solvent to the fourth solvent is (2-4):(6-8); (3) the structure directing agent comprises at least one of tetraphenyl-p-phenylenediamine, aniline, benzidine, sodium dodecyl sulfate, hexadecyltrimethylammonium bromide, polyvinylpyrrolidone or polystyrene; (4) The metal in the metal powder includes at least one of Zn, Cd, Mn, Cu, Ni, Pb, Pt or Au; (5) adjusting the pH value to 8.5-9.5; (6) the freeze-thaw cycle treatment is repeated 1 to 3 times; (7) The freezing temperature is -60 to -80°C and the freezing time is 30 to 60 minutes; (8) The drying temperature is 110-120°C and the drying time is 2-4 days.

10. The method for preparing the negative electrode material according to claim 4, characterized in that: The preparation method of the metal sulfide quantum dots comprises: The metal source A and the metal source B are mixed in a fifth solvent and heated to a first temperature; then a sulfur source is added and heated to a second temperature, and metal sulfide quantum dots are obtained after reaction.

11. The method for preparing the negative electrode material according to claim 10, characterized in that: The method for preparing metal sulfide quantum dots satisfies at least one of the following characteristics (1) to (6): (1) The metal source A and the metal source B independently include at least one of metal hydrochloride, metal sulfate, metal nitrate, metal oxide, metal carbonate, metal phosphate, metal borate, metal chromate, and metal molybdate; the metal includes at least one of Zn, Cd, Mn, Fe, Co, and In; (2) The volume molar ratio of the metal source A, the metal source B and the fifth solvent is (1-3 moL): (1-3 moL): (15-25 L); (3) The molar ratio of the metal source A to the sulfur source is (1-3):2; (4) The first temperature is 150-170°C; (5) The second temperature is 175-190°C; (6) The reaction time is 1 to 3 hours.

12. A battery, comprising a negative electrode sheet, wherein the negative electrode sheet comprises a negative electrode material, characterized in that: The negative electrode material is the negative electrode material according to any one of claims 1 to 3 or the negative electrode material prepared by the preparation method according to any one of claims 4 to 11.

Citation Information

Patent Citations

  • CsPbBr3-xIx quantum dot@COF-5 composite photocatalytic material, and preparation method and application thereof

    CN113856755A

  • Preparation method and application of silicon quantum dot SiQDs / COFBTCA-PA with covalent organic framework as carrier

    CN115188954A

  • Metal quantum dot / hard carbon negative electrode material and preparation method thereof

    CN116169288A

  • Self-supporting electrode of urea fuel cell and preparation method of self-supporting electrode

    CN117352751A

  • Carbon quantum dot modified high-conductivity covalent organic framework composite material and preparation method thereof

    CN118522864A

Cited By

  • Lithium sulfide nano-composite positive electrode material with high reaction kinetics and preparation method and application of lithium sulfide nano-composite positive electrode material

    CN120341265A